Steam-biogas reforming over a metal-foam-coated (Pd–Rh)/(CeZrO2–Al2O3) catalyst compared with pellet type alumina-supported Ru and Ni catalysts. (December 2015) - Roy, Partho S.; Park, Chan S.; Raju, Arun S.K.; Kim, Kiseok
Highlights: SBR, SMR and DMR processes were experimentally evaluated with a focus on reactant conversion and product distribution. The Pd–Rh catalyst performed better than the commercial catalysts for SBR and other reforming processes. Net CO2 reduction was achieved over Pd–Rh catalyst at temperatures above 1010 K. Abstract: Metal-foam-coated 0.09 wt% [Pd(7)–Rh(1)]/(CeZrO2 –Al2 O3 ) catalyst was compared with commercially available alumina-supported 8.0 wt% Ru and 13.0 wt% Ni catalysts for steam reforming of a model biogas. The experiments were conducted in a tubular reactor using a feedstock with the steam-to-methane ratio of 1.50 at 1 atm pressure and 20, 000 h −1 GHSV. CH4 reforming reactions by steam alone and by CO2 alone were also studied over these catalysts in order to explain the catalyst activity. The Pd–Rh catalyst is superior in a number of ways, including better activity for CH4 and CO2 conversion in spite of much less ingredient loading per unit volume. The Pd–Rh catalyst also exhibited higher syngas production index [(H2 LHV + CO LHV)/(Feed CH4 LHV)], lower syngas H2 /CO ratio and coke formation. The results were supported by BET measurement, CO chemisorption and electron microscopy. The experimental results demonstrate that the metal-foam-coated Pd–Rh/(CeZrO2 –Al2 O3 ) catalyst performs better for syngas production through steam-biogas reforming compared to the Ru and Ni catalysts.